Predictive research of 5-hydroxytryptamine in severity of severe community-acquired pneumonia - HE Quan, LIU Dan-yu, YE Jun, ZHANG Yan-li, ZHU Hua-dong, JIANG Cheng-yu, XU Jun (Jichu yixue yu linchuang, 2020)
Objective To search for potential prognostic markers for severe community-acquired pneumonia (SCAP) using non-targeted metabolomics. Methods Testing plasma samples from 30 healthy people and 68 SCAP patients (all collected from January 2015 to June 2019 at Peking Union Medical College Hospital) by liquid chromatography mass spectrometry (LC-MS). According to clinical prognosis, patients were divided into survive group (n=49) and non-survive group (n=19). OPLS-DA (multivariate statistical analysis) and Kruskal Wallis Test (single variable statistical analysis) were used to identify differential metabolites. Correlation analysis of clinical indicators and prognostic analysis were also used for differential metabolites. Results Totally 3 463 metabolites were detected in healthy people and SCAP patients by LC-MS. Among them, 126 metabolites were screened out by OPLS-DA andKruskal Wallis Test analysis methods. Prognostic analysis showed that the quantity of 5-hydroxytryptamine(5-HT) was significantly different between survive group and non-survive group (P＜0.05, AUC＞0.75). Correlation analysis of clinical indicators showed that 5-HT was positively correlated with oxygenation index (OI) and negatively correlated with acute physiology and chronic health evaluation Ⅱ (APACHE Ⅱ) score. Conclusions The 5-HT as a potential prognostic marker for SCAP, may predict the prognosis of SCAP patients.